Dracula's other modernity: liberalism and 'Life' at the fin de siècle. Issue 2 (4th March 2021) - Macleod, Jock
ABSTRACT: Much of the scholarship on Dracula (1897) has analysed it as a symptom of various anxieties at the core of late Victorian scientific and technological modernity. In this approach, Stoker's liberalism in the novel has been read as part of the fragile rational world seeking to suppress the desires and fears of the erotic and other affective forces. This paper takes a different approach. In this paper, I examine the novel through the lens of a strand of modernity that developed around the concept of 'Life'. 'Life' was conceived as an internal generative power of emergence and became a key metaphor for late Victorian progressive liberals, for whom it signified progress as continuously emerging potential, always free from pre-determination. I examine the modernity of 'Life' in Part I of the paper and take up its relevance to nineteenth-century liberalism. In Part II, I use modernity's discourse of 'Life' as a frame for my analysis of Dracula 's liberalism.